CLINICAL СASE OF INFLUENZA A(H1N1) COMPLICATED WITH ACUTE DISSEMINATED ENCEPHALOMYELITIS - L. N. Mazankova; T. A. Chebotareva; E. P. Koval; M. A. Antsupova; A. V. Belaya (LLC "Diagnostics and Vaccines", 2018)
The defeat of the central nervous system in influenza reflects the properties of both the pathogen itself and the complex pathogenetic mechanisms of the influenza infectious process.  Existing modern  theories do not fully explain the pathological conditions of influenza in the central nervous system, which is still accompanied by ambiguous clinical arguments about the direct cytopathic effect of the influenza virus on neural tissue with the development of encephalitis. Another rare complication of the flu is acute disseminated encephalomyelitis. The autoimmune mechanism of the development of this disease is universally recognized, despite the continuing difficulties of diagnosis in the absence of oligoclonal antibodies in blood plasma and spinal cerebral fluid in the majority of patients.